Microstructural Characterization and Mechanical Properties of Similar and Dissimilar Al Alloys Joined using Friction Stir Welding - Hassan, Kharia Salman (Al-Khwarizmi Engineering Journal, 2018)
The influence of pre- shot peening and welding parameters on mechanical and metallurgical properties of dissimilar and similar aluminum alloys AA2024-T3 and AA6061-T6 joints using friction stir welding have been studied. In this work, numbers of plates were equipped from sheet alloys in dimensions (150*50*6) mm then some of them were exposed to shot peening process before friction stir welding using steel ball having diameter 1.25 mm for period of 15 minutes. FSW joints were manufactured from plates at three welding speeds (28, 40, 56 mm/min) and welding speed 40mm/min was chosen at a rotating speed of 1400 rpm for welding the dissimilar pre- shot plates. Tow joints were made at rotational speed of 1000 rpm and welding speed of 40m/min from shot and without shot peening plats. Welding temperature was measured in three zones using thermocouple. Micro hardness (HV) and tensile tests were performed to evaluate the mechanical characteristic of the joints. The results show a decay in mechanical qualities when the welding speed was increased and the best result was at (28) mm/min and the opposite result was obtained when rotational speed increased and pre-shot contributed in improving of this decay at 88% of welding speed (40) mm/min and 98%  at the rotational speed of 1000 rpm.